Identifikasi Kandungan Senyawa Aktif dan Penentuan Massa Jenis Ekstrak Etanol Daun Jambu Air (Syzygium aqueum) - Naufal, Muhammad Ariq; Susianti; Daulay, Suryani Agustina; Carolia, Novita (CV. Jasa Sukses Abadi, 2024)
Water apple (Syzygium aqueum) is a plant widely utilized by publics for both consumption and medicinal purposes. Traditionally, it is used as an alternative treatment for diarrhea, headaches, and cough. The method to maximize the potential of water apple leaves is by extracting the active compounds in it. These extracts have potential as antioxidants, anti-inflammatory, anti-cholesterol, antidiabetics, and antidiarrheal agents. Previous studies have shown that water apple leaves contain various active compounds such as alkaloids, flavonoids, terpenoids, saponins, and phenolics. This research aimed to analyze the active compounds and determine the density of the water apple leaf extract. The study was conducted as a laboratory-based experimental research at the Botany Laboratory, FMIPA University of Lampung. The method employed was maceration of water apple leaves using 96% ethanol as a solvent, followed by qualitative phytochemical tests and density determination. Qualitative tests conducted included assessments for flavonoids, terpenoids, tannins, saponins, phenolics, alkaloids, and steroids. The density of the extract was determined by measuring the mass of the extract using an analytical balance and dividing it by its volume. The results showed that maceration using 96% ethanol yielded 110.62 grams of extract with a yield percentage of 11.062%. Phytochemical tests revealed the ethanol extract contained flavonoids, phenolics, tannins, saponins, alkaloids, and steroids. The density of the ethanol extract was calculated to be 0.9209 g/mL.